Context evaluation of the implementation of science, technology, engineering and mathematics education in lower secondary school - Loh, Su Ling (2020)
Science, Technology, Engineering, and Mathematics (STEM) education is one of the learning approaches in the new Secondary School Standard Curriculum (Kurikulum Standard Sekolah Menengah, KSSM) in Malaysia. Many efforts are carried out in promoting awareness and interest in STEM education in primary and secondary schools by various sectors. However, not many studies are done to evaluate the context of STEM education implementation. Context evaluation guides the choice of interventions and justifies any decisions made that addresses the gaps and using the available opportunities for the implementation of a STEM education programme. It facilitates the formulation of the objectives of STEM education programmes. Otherwise, activities, programmes, and projects on integrated STEM education will just be carried out without meeting the needs and thus not achieving the desired result. This study presents a qualitative case study of context evaluation of STEM education at the lower secondary school level. Three schools were selected through a purposive sampling strategy to reveal some critical shared patterns. Open-ended interviews were conducted among lower secondary Science, Mathematics, Basic Computer Science, and Design of Technology subject teachers. Data were also collected through the analysis of the individual STEM subjects’ curriculum standards documents and yearly teaching plans. The yearly teaching plans are consolidated and translated into a planned curriculum map to identify gaps and possibilities of integration. The findings revealed the need for STEM subjects’ integration and more emphasis on contextual problem-solving. The lack of pedagogical content knowledge (PCK), time constraint, lack of teachers’ collaboration, lack of STEM expertise, lack of resources and facilities, and student ability are the causal factors revealed in the study. Opportunities such as 21st century learning skills, teachers’ potential, and the possibilities of standard-based STEM integration are also identified. Four objectives of a STEM education programme are formulated to address the problems and complement the available opportunities. Implications of the study are discussed, and several recommendations are presented in the hope of improving the implementation of STEM education at the lower secondary school level.